2022
DOI: 10.3390/jcm11164787
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for Anorexia Nervosa during the COVID-19 Pandemic in France: A Nationwide Population-Based Study

Abstract: The COVID-19 pandemic has had a detrimental impact on mental health, including on food-related behaviors. However, little is known about the effect of the pandemic on anorexia nervosa (AN). We sought to assess an association between the COVID-19 pandemic and a potential increase in hospitalizations for AN in France. We compared the number of hospitalizations with a diagnosis of AN during the 21-month period following the onset of the pandemic with the 21-month period before the pandemic using Poisson regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Several factors may help explain discrepancies between our results and broader epidemiological findings. Firstly, we have seen a global rise in levels of ED pathology during the Covid‐19 pandemic (Chauvet‐Gelinier et al, 2022; Lin et al, 2021; Monteleone et al, 2021; Spettigue et al, 2021; Tavolacci et al, 2021), especially in young girls presenting with full and subthreshold AN (Agostino et al, 2021; Haripersad et al, 2021; Meier et al, 2022; Taquet et al, 2022). Like numerous countries globally, Norway's public health care system observed a significant surge in EDs during the pandemic, the period when this study's data was gathered.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may help explain discrepancies between our results and broader epidemiological findings. Firstly, we have seen a global rise in levels of ED pathology during the Covid‐19 pandemic (Chauvet‐Gelinier et al, 2022; Lin et al, 2021; Monteleone et al, 2021; Spettigue et al, 2021; Tavolacci et al, 2021), especially in young girls presenting with full and subthreshold AN (Agostino et al, 2021; Haripersad et al, 2021; Meier et al, 2022; Taquet et al, 2022). Like numerous countries globally, Norway's public health care system observed a significant surge in EDs during the pandemic, the period when this study's data was gathered.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has accelerated this process. Several studies have pointed out a marked increase in new diagnoses and severity of preexisting cases of AN with higher rates of hospital admission during the first wave of the COVID-19 pandemic and lockdown [13][14][15].…”
Section: Prevalencementioning
confidence: 99%
“…Most research has focused on the putative links between adverse psychological triggers (e.g. confinement, social isolation, or closure of non-essential activities) and self-harm behaviors in vulnerable populations ( Farooq et al 2021 ; Chauvet-Gelinier et al 2022 ). In addition, a meta-analysis of studies conducted between 1910 and 2020, including the SARS-Cov-2 pandemic, showed that the link between historical epidemics and suicidal behavior did not appear to be strong, but also highlighted the lack of qualitative and quantitative data on the issue ( Rogers et al 2021 ; Zhu, Li, et Xu 2022 ).…”
Section: Introductionmentioning
confidence: 99%